Influence of clay amendment on soil physical properties and threshold friction velocity within a disturbed crust cover in the inland pacific Northwest - Pi, Huawei; Huggins, David R.; Sharratt, Brenton (Soil & tillage research, 2020)
[Display omitted] •Soil clay content is a primary soil component influencing wind erosion•This study assessed the effect of clay amendment on threshold friction velocity (u*t)•Clay amendment didn’t directly impact u*t, but did impact crust, aggregate properties•Threshold friction velocities were sensitive to lower clay amendments (<2%)•Clay amendment directly impact on aggregate GMD due to crust crushing energy Soil wind erosion is initiated when the surface friction velocity (u*) exceeds the threshold friction velocity (u*t) of soils. Soil clay content is a primary soil component influencing soil erosion. Few studies have tested the effect of clay amendment on u*t, especially in the inland Pacific Northwest (iPNW) where there is a high wind erosion risk due to the arid and semi-arid environment. The objective of this study was therefore to evaluate the effect of soil clay amendment (Wyoming bentonite) on u*t. Bentonite clay was added to four soil types prior to wetting the treated soil to create complete crust cover. The treated soil was then subject to simulated tillage to create an erodible soil surface before determining u*t in a wind tunnel. Clay amendment did not directly impact u*t, but did impact crust and aggregate properties. Crust crushing energy appeared to increase binomially with increasing clay amendment. Statistically significant relationships were found between crust crushing energy and aggregate geometric mean diameter (GMD) and between aggregate GMD and u*t. Clay amendment therefore appeared to indirectly impact u*t due to its impact on aggregate GMD. Our results were similar to previous studies that clay amendment can be effective in stabilizing erosive sandy soil ecosystems.